INCREASING THE RESISTANCE OF WELDING JOINTS IN MEDIUM CARBON STEEL PRIOR TO CTACK FORMATION - Клочко, Оксана; Дерябкіна, Євгенія (SWorldJournal, 2024)
Below, we study the effect of heat input on the resistance against crystallization cracks of weldments, that appears due to presence of the main medium-carbon material in the weld metal. The amount of heat input inside the first and second layers have be